2013
DOI: 10.2140/pjm.2013.261.257
|View full text |Cite
|
Sign up to set email alerts
|

Geography of simply connected nonspin symplectic 4-manifolds with positive signature

Abstract: We construct new families of closed simply connected nonspin irreducible symplectic 4-manifolds with positive signature that are interesting with respect to the geography problem. Note that e(M) and σ (M) are in turn completely determined by χ h (M) and c 2 1 (M), that is, e(M) = 12χ h (M) − c 2 1 (M) and σ (M) = c 2 1 (M) − 8χ h (M). When M is a complex surface, χ h (M) is the holomorphic Euler characteristic of M while c 2 1 (M) is the square of the first Chern class of M. The classical "geography problem" i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…In terms of the symplectic geography problem, the work in [3,6] concluded that there exists an irreducible symplectic 4-manifold and infinitely many irreducible non-symplectic 4-manifolds with odd intersection form that realize the following coordinates (χ, c 2 1 ) when 0 ≤ c 2 1 < 8χ. A similar results for the nonnegative signature case were obtained in [7,4]. We would like to remark that throughout this paper, we consider the geography problem for non-spin symplectic and smooth 4-manifolds.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…In terms of the symplectic geography problem, the work in [3,6] concluded that there exists an irreducible symplectic 4-manifold and infinitely many irreducible non-symplectic 4-manifolds with odd intersection form that realize the following coordinates (χ, c 2 1 ) when 0 ≤ c 2 1 < 8χ. A similar results for the nonnegative signature case were obtained in [7,4]. We would like to remark that throughout this paper, we consider the geography problem for non-spin symplectic and smooth 4-manifolds.…”
Section: Introductionsupporting
confidence: 74%
“…The next theorem will be used to produce an infinite family of pairwise nondiffeomorphic, but homeomorphic simply connected 4-manifolds. The following corollary follows from the above Theorems, and proof can be found in [4]. Corollary 3.8.…”
Section: Luttinger Surgeries On Product Manifoldsmentioning
confidence: 87%
See 2 more Smart Citations
“…It was shown in [2] that for every integer q 25, there exists an irreducible symplectic 4manifold Y (q) that is homeomorphic but not diffeomorphic to (2q − 1)(CP 2 #CP 2 ). Moreover, it was shown in [1] that each Y (q) contains a symplectic torus T of self-intersection 0 such that π 1 (Y (q) \ T ) = 0. Similarly, it was shown in [3] that for every integer p 138, there exists an irreducible symplectic 4-manifold Z(p) that is homeomorphic but not diffeomorphic to (2p − 1)(S 2 × S 2 ) and contains a symplectic torus T of self-intersection 0 such that π 1 (Z(p) \ T ) = 0.…”
Section: Irreducible Building Blocksmentioning
confidence: 99%